Conception of wheeled mobile robots with reconfigurable control using integrate prototyping - Rosario, J. M.; Pegoraro, Renê [UNESP]; Ferasoli, H. [UNESP]; Dumur, D. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
With the fast innovation of the hardware and software technologies using rapid prototyping devices, with application in the robotics and automation, more and more it becomes necessary the development of applications based on methodologies that facilitate future modifications, updates and enhancements in the original projected system. This paper presents a conception of mobile robots using rapid prototyping, distributing the several control actions in growing levels of complexity and using resources of reconfigurable computing proposal oriented to embed systems implementation. Software and the hardware are structuralized in independents blocks, with connection through common bus. The study and applications of new structures control that permits good performance in relation to the parameter variations. This kind of controller can be tested on different platform representing the wheeled mobile robots using reprogrammable logic components (FPGA). © 2006 IEEE.
Keywords: Control; Embedded systems; Mechatronics; Mobile robot; Prototyping; Control theory; Field programmable gate arrays (FPGA); Software prototyping; Independents blocks; Reconfigurable computing; Wheeled mobile robots; Mobile robots